Sustentabilidade organizacional: o processo de construção do Relatório de Global Reporting Iniciative (GRI) para a Unimed Bauru sob a ótica das Relações Públicas - Gonçalves, Tamires Löw [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The paper describes the ways of reporting business management, employing the model of sustainability report called the Global Reporting Initiative - GRI. This makes use of indicators based on the concept called Triple Bottom Line, which takes into account the economic, social and environmental. The study points out theoretical positions and concepts that have demonstrated an understanding of this issue and especially emphasizes the presence and experience of Public Relations in the environment of organizational communication, especially in the sphere of quality management activities, coupled with the operational processes and sustainable principles. The discussion is exemplified by a case study of quality management activities, coupled with the operational processes and sustainable principles. The discussion is exemplified by a case study of the Health Cooperative Medical Unimed Bauru that involves the process of preparing the report in GRI model of sustainability, held earlier in the year 2011

O trabalho descreve os caminhos da elaboração de relatórios de gestão empresarial, que empregam o modelo de relatório de sustentabilidade denominado de Global Reporting Iniciative – GRI. Este se utiliza de indicadores baseados no conceito denominado de “Triple Botton Line”, o qual leva em conta as dimensões econômica, social e ambiental. O estudo pontua posturas teóricas e conceitos que tem evidenciado a compreensão desta temática e, sobretudo, destaca a presença e a vivência do profissional de Relações Públicas no ambiente da comunicação organizacional, especialmente na esfera da atividade de gestão da qualidade organizacional, aliada aos processos operacionais e aos preceitos sustentáveis. A discussão é exemplificada por um estudo de caso da Cooperativa de Saúde Médica Unimed Bauru que envolve o processo de elaboração do relatório de sustentabilidade no modelo GRI, realizado no início do ano de 2011
Keywords: Relações publicas; Comunicação nas organizações; Desenvolvimento sustentável; Public relations; Communication in organizations; Sustainable development